2008
DOI: 10.1037/h0099353
|View full text |Cite
|
Sign up to set email alerts
|

Fair game: The intuitive economics of resource exchange in four-year olds.

Abstract: Four-year olds participated in versions of adult bargaining games (the ultimatum and dictator games) that were designed to test for understanding of fairness, reciprocity, and altruism and were adapted to be appropriate for their age group. They were also given endowment and theory of mind tasks. The results showed that young children were similar to adults in their preferences for fairness although they tended to make more altruistic offers. They also demonstrated some ability to think strategically about off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
2
36
0
3
Order By: Relevance
“…However, other studies have reported marginally positive to positive correlations among children of a similar age range playing the same game (Rochat et al, 2009;Wu & Su, 2014). If a recipient was entitled to accept or reject the shared portion of an endowment, ToM seemed to facilitate sharing in 4-to 6-year-olds (Takagishi et al, 2010) but not in 4-and 5-year-olds (Lucas et al, 2008). However, none of these studies included kin.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, other studies have reported marginally positive to positive correlations among children of a similar age range playing the same game (Rochat et al, 2009;Wu & Su, 2014). If a recipient was entitled to accept or reject the shared portion of an endowment, ToM seemed to facilitate sharing in 4-to 6-year-olds (Takagishi et al, 2010) but not in 4-and 5-year-olds (Lucas et al, 2008). However, none of these studies included kin.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, higher levels of sympathy in 4-year-old children were associated with larger amounts of sharing in dictator games (Ongley & Malti, 2014). However, ToM was also found to be unrelated to children's performance in sharing games (Lucas et al, 2008;Mulvey et al, 2016) and was even related to less sharing because children with ToM might know there were no consequences for not sharing (Cowell, Samek, List, & Decety, 2015). Whereas ToM appears to be cognitively necessary for allocating resources to others because knowing how others feel facilitates considering their interests, kin altruism may be exercised without needing to understand other people's perspectives because one can be unilaterally benevolent toward kin (Lu & Chang, 2009).…”
Section: Altruism and Theory Of Mindmentioning
confidence: 92%
See 1 more Smart Citation
“…Stickers (Benenson, Pascoe, & Radmore, 2007;Blake & Rand, 2010;Gummerum, Hanoch, Keller, Parsons, & Hummel, 2010;Lucas, Wagner, & Chow, 2008), food (Brownell, Svetlova, & Nichols, 2009;Fehr & Fischbacher, 2003;House et al, 2012;Markovits, Benenson, & Kramer, 2003), and money (Gummerum, Keller, Takezawa, & Mata, 2008;Harbaugh, Krause, & Liday, 2003;Leman et al, 2009) have been used to investigate cooperative behavior in children, in a variety of experimental designs. However, to our knowledge only one study have recently compared the effect of different kind of resources on cooperation in 3-year-old children and have found no differences (Warneken, Lohse, Melis, & Tomasello, 2010).…”
mentioning
confidence: 99%
“…Resource distribution tasks like the Dictator Game (DG) have been used to examine fairness and prosocial behavior in young children (Aguilar-Pardo, Martínez-Arias, & Colmenares, 2013; Benenson, Pascoe, & Radmore, 2007;Benozio & Diesendruck, 2015;Blake & Rand, 2010;Chen, Zhu, & Chen, 2013;Gummerum, Hanoch, Keller, Parsons, & Hummel, 2010;Kogut, 2012;Lucas, Wagner, & Chow, 2008;Ongley & Malti, 2014) and typically generate greater variation in responses than binary forced-choice measures. Blake and Rand (2010) have also successfully used the DG to demonstrate that children use their own a priori explicitly stated preferences to guide how they distribute resources.…”
Section: Introductionmentioning
confidence: 99%